Partitioning and Translocation of Dry Matter and Nitrogen During Grain Filling in Spring Barley Varieties and Their Roles in Determining Malting Quality - Barmeier, Gero; Hu, Yuncai; Schmidhalter, Urs (Frontiers in Plant Science, 2021)
To meet the strict requirements for malting quality of both grain size and protein content for malting barley, a better understanding of the partitioning and remobilization of dry matter (DM) and nitrogen (N) from individual vegetative organs during grain filling may contribute to achieving a balance of both quality parameters to satisfy the malting criteria of the brewing industry. A two-year experiment including 23 spring malting barley varieties was carried out to determine the DM and N partitioning in different organs at anthesis and maturity and to estimate their remobilization to grains. In contrast to the genetic variation of the 23 barley varieties, the year effect was the most important single factor influencing the DM and N accumulation at pre-anthesis, and the DM and N translocation from their reserves at pre-anthesis. Post-anthesis assimilates accounted for 71-94% of the total grain yield among the barley varieties in 2014 and 53-81% in 2015. In contrast, the N reserved in vegetative tissues at anthesis contributed to barley grain N from 67% in the variety Union to 91% in the variety Marthe in 2014, and 71% in the variety Grace to 97% in the variety Shakira in 2015. Our results concluded that photosynthetically derived assimilates at post-anthesis played an important role in determining grain size, whereas N reserves at pre-anthesis and N remobilization at post-anthesis probably determined the grain protein content of the malting barley. To achieve a high quality of malting barley grains in both grain size and protein content simultaneously, balancing photosynthetic assimilates at post-anthesis and N reserves at pre-anthesis and N remobilization should be considered as the strategies for the combination of the selection of spring malting barley varieties together with agronomic N management.